2016
DOI: 10.1039/c5cc08945j
|View full text |Cite
|
Sign up to set email alerts
|

NHPI and palladium cocatalyzed aerobic oxidative acylation of arenes through a radical process

Abstract: The NHPI and palladium cocatalyzed radical oxidative acylation of arenes with aldehydes and alcohols as acyl equivalents via selective C-H functionalization has been described. Molecular oxygen, the most environmentally friendly oxidant, was used as the terminal oxidant in this catalytic cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 82 publications
(5 reference statements)
0
22
0
Order By: Relevance
“…Due to stabilization of the SOMO by the aryl ring, 1 a′ undergoes deprotonation to yield the aryl radical 1 a′′ . Similarly, the morpholinyl radical 2 a′ is generated by successive SEO of the nitrogen atom and deprotonation under synergistic cooperation of copper and the hydrogen atom transfer (HAT) catalyst NHPI . Under the cooperative actions of electronic and steric effects, radical 2 a′ selectively couples with 1 a′′ at the site para to the nitrogen atom to afford the 6‐aminotetrahydroquinoxaline 3 aa ‐ 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to stabilization of the SOMO by the aryl ring, 1 a′ undergoes deprotonation to yield the aryl radical 1 a′′ . Similarly, the morpholinyl radical 2 a′ is generated by successive SEO of the nitrogen atom and deprotonation under synergistic cooperation of copper and the hydrogen atom transfer (HAT) catalyst NHPI . Under the cooperative actions of electronic and steric effects, radical 2 a′ selectively couples with 1 a′′ at the site para to the nitrogen atom to afford the 6‐aminotetrahydroquinoxaline 3 aa ‐ 1 .…”
Section: Resultsmentioning
confidence: 99%
“…[8b, 15] Due to stabilization of the SOMO by the aryl ring, 1a' undergoes deprotonation to yield the aryl radical 1a''.S imilarly,t he morpholinyl radical 2a' is generated by successive SEO of the nitrogen atom and deprotonation under synergisticc ooperation of coppera nd the hydrogen atom transfer (HAT)c atalyst NHPI. [16] Undert he cooperative actions of electronic and steric effects, radical 2a' selectively couples with 1a'' at the site para to the nitrogena tom to afford the 6-aminotetrahydroquinoxaline 3aa-1.F urther-more,t he a-carbon radical [17] 3aa-2 is formed by SEO of the nitrogen atom of the morpholinyl unit in 3aa-1 followedb y isomerization and deprotonation (from 3aa-1 to 3aa-1' and 3aa-1''). Finally,c ross-couplingb etween 3aa-2 and 2a' followed by athermodynamically favorable dehydroaromatization of the coupling adduct 3aa-3 gives rise to the desired product 3aa.A sw ell as the radical and radicalc ross-coupling reaction modes, nucleophilica ddition of morpholine to the in situ generated aryl radical cation might also be involved in the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…To optimize the yield of the ortho ‐amidated derivative, we screened several parameters (Table ). We found that complexes of transition metals, such as ruthenium,, palladium,,, and cobalt,,,, which are known to be effective in direct C−H bond functionalization, were not successful in this transformation (Table ,entries 4–6). Control experiment also confirmed that the rhodium catalyst was essential for this reaction (Table , entry 7).…”
Section: Resultsmentioning
confidence: 99%
“…[31] Furthermore, aryl aldehydes and ben-zyl alcohols could also be used as acyl equivalents for C-H acylation with O 2 as the oxidant. [32] Scheme 16 PdCl 2 and NHPI cocatalyzed Csp 2 -H hydroxylation Scheme 17 Pd-catalyzed aerobic oxidative C-H acylation with active radical reactants By a similar radical strategy, C-H nitration products could be obtained selectively with commercially available tert-butyl nitrite (TBN) and O 2 as the precursors of active NO 2 radical (Scheme 18a). [31] It is noted that pyridine, pyrimidine, pyrazole, pyridol, pyridylketone, oxime, and azo groups, can be used as directing groups in this C-H nitration.…”
Section: Methodologies Through C-h Bond Cleavagementioning
confidence: 99%